Shear Stress Rescued the Neuronal Impairment Induced by Global Cerebral Ischemia Reperfusion via Activating PECAM-1-eNOS-NO Pathway - Gao, Jing-Quan; Wang, Peng; Yan, Jun-Wei; Ba, Li-Na; Shi, Pi-Long; Wu, Hong-Mei; Guan, Xue-Ying; Cao, Yong-gang; Sun, Hong-Li; Mao, Xiao-Yuan (Frontiers in Cell and Developmental Biology, 2021)
Microvessel hypoperfusion of ischemic regions down regulates shear stress on brain microvascular endothelial cells (BMECs) and is associated with abnormal expression of PECAM-1 after global cerebral ischemia/reperfusion (I/R) injury. Here, we identified novel pathophysiologic and rehabilitative procedures specific to shear stress in microvascular endothelial cells in response to global cerebral I/R injury. We found that the decrease in cerebral blood flow of gerbils after global cerebral I/R injury reduces shear stress, and the abnormal change in shear stress leads to microvascular endothelial cell and neuron damage. Nevertheless, suitable high levels of shear stress contribute to rescuing the dysfunction and malformation of brain microvascular endothelial cells via regulating the PECAM-1-eNOS-NO pathway to enhance nitric oxide release, decrease the expression of caspase-3 to reduce apoptosis, and improve the shear-adaptability of endothelial cells, thereby playing a protective role in the gerbil brain.